スポーツに関連した口腔顎顔面外傷における臨床的検討 - 渡邊, 正章; 大熊, 里依; 狩野, 正明; 小池, 尚史; 管野, 貴浩; 吉松, 英樹; 関根, 浄治; 辰巳, 博人 (口腔顎顔面外傷 : 日本口腔顎顔面外傷学会誌, 2017)
Introduction: The number of maxillofacial injuries sustained during sports is increasing in line with the growing number of people engaging in sports activities. Sports are one of the frequent causes of oral and maxillofacial trauma. To elucidate the characteristics of oral and maxillofacial injuries, we retrospectively examined cases of sports injuries in our department.Patients and Methods: Three hundred fifty-nine patients with oral and maxillofacial injuries between April 2012 and March 2016, and 64 patients （17.8%） with these injuries occurring during sports presenting at our department.Result: As for oral and maxillofacial injuries occurring during sports, most injuries were in male subjects, with a male to female ratio of 3.3:1, and the most frequently injured were teens （67.2%）, followed by those under ten （12.5%） and those in their twenties （12.5%）. By type of sport, injuries were most common in baseball （39.1%）, followed by basketball （18.8%）, soccer （12.5%）, and volleyball （6.3%）. Regarding type of injury, fracture was the most frequent （35.9%）, such as jaw fracture and orbital floor fracture, followed by tooth injury and soft tissue injury. Treatments were usually performed, and the patients made an uneventful recovery and regained their pre-accident maxillofacial function.Conclusion: It appears that oral and maxillofacial injuries occur frequently in the popular sports such as baseball, soccer, basketball and volleyball. We consider it is important to recognize characteristic trauma for prompt diagnosis and treatment of these injuries. It is necessary to wear a mouthguard, faceguard, and so on to prevent some sports injuries such as fracture and tooth injuries.